Re-Imagined Universities and Global Citizen Professionals : International Education, Cosmopolitan Pedagogies and Global Friendships - George, Shanti; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Universities are increasingly criticised for their limited relevance to a globalized and unequal world. Drawing on research from over 27 countries, this book outlines new directions for universities and the need to rethink the education that they provide based on the experiences of schools of international development studies.
Keywords: Science; Science; Science, general